Studies on neotropical Phasmatodea I: A remarkable new species of Peruphasma Conle & Hennemann, 2002 from Northern Peru (Phasmatodea: Pseudophasmatidae: Pseudophasmatinae) - Conle, Oskar V.; Hennemann, Frank H. (Zootaxa, 2005)
Peruphasma schultei n. sp., a remarkable new phasmid from the Cordillera del Condor in Northern Peru is described and illustrated from both sexes and the eggs. It is the first species of Peruphasma Conle & Hennemann, 2002 known to have rudimentary tegmina and alae. The original specimens were collected by Dipl. Biol. Rainer Schulte (INIBICO NGO, Tarapoto, Peru) to whom it is dedicated. Brief information on its biology and breeding are provided as well. Peruphasma picturata (Redtenbacher, 1906) is re-transferred to Autolyca Stål, 1875 and the type-locality “Chile” is shown to be wrong.